Brain drain in the age of mass migration: Does relative inequality explain migrant selectivity? - Yvonne Stolz; Jörg Baten (Center for Economic Studies and ifo Institute (CESifo), 2012)
Brain drain is a core economic policy problem for many developing countries today. Does relative inequality in source and destination countries influence the brain-drain phenomenon? We explore human capital selectivity during the period 1820-1909.We apply age heaping techniques to measure human capital selectivity of international migrants. In a sample of 52 source and five destination countries we find selective migration determined by relative anthropometric inequality in source and destination countries. Other inequality measures confirm this. The results remain robust in OLS and Arellano-Bond approaches. We confirm the Roy-Borjas model of migrant self-selection. Moreover, we find that countries like Germany and UK experienced a small positive effect, because the less educated emigrated in larger numbers.
Keywords: F22; J40; I21; N30; 330; international migration; labor markets; human capital; economic history; Brain Drain; Internationale Wanderung; Humankapital; Anthropologie; Soziale Ungleichheit; Wirtschaftsgeschichte; Welt; Großbritannien; Deutschland (bis 1945)